2010
DOI: 10.1007/s00028-010-0081-z
|View full text |Cite
|
Sign up to set email alerts
|

Periodic solutions of fractional differential equations with delay

Abstract: Artículo de publicación ISIIn this paper, we give a necessary and sufficient conditions for the existence and uniqueness of periodic solutions of inhomogeneous abstract fractional differential equations with delay. The conditions are obtained in terms of R-boundedness of operator-valued Fourier multipliers determined by the abstract model.FONDECYT 1100485 FONDECYT de Iniciacion 1107504

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
(18 reference statements)
4
35
0
Order By: Relevance
“…It is clear that the definition (2.3) coincides with the definition (2.1) when α = 1, and D = D 1 . See [18] for an equivalent definition of the fractional derivative D α on L p (T, X).…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that the definition (2.3) coincides with the definition (2.1) when α = 1, and D = D 1 . See [18] for an equivalent definition of the fractional derivative D α on L p (T, X).…”
Section: Preliminariesmentioning
confidence: 99%
“…[1][2][3]8,[10][11][12][13][14][15][16][17][18]20,21]). They are useful in the study of the well-posedness of differential equations on Banach spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of periodic solutions is often a desired property in dynamical systems, constituting one of the most important research directions in the theory of dynamical systems, with applications ranging from celestial mechanics to biology and finance. Fractional differential equations (FDEs) are the most important generalizations of the field of ODE [17][18][19][20][21]. Recent investigations in physics, engineering, biological sciences and other fields have demonstrated that the dynamics of many systems are described more accurately using FDEs, and that FDE with delay are often more realistic to describe natural phenomena than those without delay.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic solution fractional differential equations have been studied by many researchers. They studied periodic solutions of the equation (see [17,18])…”
Section: Introductionmentioning
confidence: 99%